QoS-aware flow scheduling for energy-efficient cloud data centre network. (6th July 2020) - Wang, Songyun; Yuan, Jiabin; Zhang, Xiaoda; Qian, Zhuzhong; Li, Xin; You, Ilsun
It is highly valuable to achieve energy-efficient cloud data centres, which always act as the basic infrastructures. This paper thus aims at reducing the energy consumption of network devices in cloud data centres by flexible flow scheduling. For such an aim, it is necessary to guarantee the flow-level performance, which is a critical requirement for quality of service (QoS) in production data centres. Hence, this paper takes both energy reduction and QoS into account for flow scheduling, and then proposes a three-phase framework to control the energy consumption for cloud data centre network (DCN) while guaranteeing flow-level performance. The core idea is to turn off the unnecessary switches off. From extensive simulations, it is shown that our solution could not only reduce about 20% of energy on average than the case with all switches on, but also maintain good flow-level performance, stability and fault tolerance simultaneously.